New perspectives in cancer biology from a study of canonical and non-canonical functions of base excision repair proteins with a focus on early steps. (19th December 2019) - Malfatti, Matilde Clarissa; Antoniali, Giulia; Codrich, Marta; Burra, Silvia; Mangiapane, Giovanna; Dalla, Emiliano; Tell, Gianluca
Abstract: Alterations of DNA repair enzymes and consequential triggering of aberrant DNA damage response (DDR) pathways are thought to play a pivotal role in genomic instabilities associated with cancer development, and are further thought to be important predictive biomarkers for therapy using the synthetic lethality paradigm. However, novel unpredicted perspectives are emerging from the identification of several non-canonical roles of DNA repair enzymes, particularly in gene expression regulation, by different molecular mechanisms, such as (i) non-coding RNA regulation of tumour suppressors, (ii) epigenetic and transcriptional regulation of genes involved in genotoxic responses and (iii) paracrine effects of secreted DNA repair enzymes triggering the cell senescence phenotype. The base excision repair (BER) pathway, canonically involved in the repair of non-distorting DNA lesions generated by oxidative stress, ionising radiation, alkylation damage and spontaneous or enzymatic deamination of nucleotide bases, represents a paradigm for the multifaceted roles of complex DDR in human cells. This review will focus on what is known about the canonical and non-canonical functions of BER enzymes related to cancer development, highlighting novel opportunities to understand the biology of cancer and representing future perspectives for designing new anticancer strategies. We will specifically focus on APE1 as an example of a pleiotropic and multifunctional BER protein.